2023
DOI: 10.3390/fermentation9040402
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Lactic Acid Bacteria in Traditional Fermented Foods in Yunnan Province, China, and Comparative Genomics of Lactobacillus plantarum

Abstract: The diversity of lactic acid bacteria (LAB) in fermented foods in Yunnan currently lacks large-scale and systematic research. A total of 638 fermented foods were collected from 84 regions in Yunnan for diversity analyses. The results show that the dominant strains in various types of fermented foods were different. Additionally, the majority of the LAB were better adapted to regions with a temperature of 15–20 °C and a humidity of 64–74%. Lactobacillus plantarum (L. plantarum) was the most abundant of all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…plantarum strains isolated from different sources. The larger genome size and GC ratio of Lactobacillus strains mean it reflects the environmental adaptability of the strains (Li et al, 2023 ). The genome-based taxonomy by TYGS revealed that it is closely related to Lp.…”
Section: Discussionmentioning
confidence: 99%
“…plantarum strains isolated from different sources. The larger genome size and GC ratio of Lactobacillus strains mean it reflects the environmental adaptability of the strains (Li et al, 2023 ). The genome-based taxonomy by TYGS revealed that it is closely related to Lp.…”
Section: Discussionmentioning
confidence: 99%
“…Yunnan Province, located in southern China, has diverse climatic and geographic conditions that create biodiversity and a unique ecological microenvironment for fermented vegetables from this region . Our previous studies have elucidated the fermentation process, flavor, and nutritional functions of fermented vegetables such as chili pepper and chayote from Yunnan Province. However, the rich microbial resources in Yunnan Province have not been fully exploited, and there is a lack of standardized production …”
Section: Methodsmentioning
confidence: 99%
“…Lactic-acid-producing bacteria are commonly called Lactobacilli (LAB). LAB form a large class of non-spore-forming, catalase-negative, Gram-positive, and facultatively anaerobic bacteria that can utilize carbohydrates to produce lactic acid [32]. LAB is beneficial to our health because they ferment many foodstuff-producing products that lower blood sugar and exert anti-inflammatory actions.…”
Section: Introductionmentioning
confidence: 99%